Analysis Juridical Public Participation Formation of Regional Regulation No. 3 of 2017 on The Implementation of The Business Entertainment In Wonosobo Regency - Amin Syarifudin; Rakhmat Bowo Suharto (Jurnal Daulat Hukum, 2019)
To set the order and comfort in the Wonosobo regency and Goverment Wonosobo regency make Region Regulation No. 3 of 2017 on the Implementation of Enterprise Entertainment in Wonosobo. This is associated with the rise of karaoke business premises in Wonosobo. But after the regulation passes reap a lot of conflict in the community. This makes the writer interested in making. Juridical Analysis of Public Participation in Formation of Regional Regulation Number. 3 of 2017 on the Implementation of Enterprise Entertainment in Wonosobo,Method of approach used in this study is a sociological juridical methods, using the principles and legal principles in reviewing, view, and analyze problems.According to Act No. 12 of 2011 Establishment Regulation Legislation. Article 96 "The public has the right to give feedback in oral and / or written in question can be done through public hearings, working visits, socialization and / or, seminars, workshops and / or discussion.In the establishment of the Regional Regulation No. 3 Of 2017 on the Implementation of Enterprise Entertainment in Wonosobo regency public participation, not maximum.Constraints in the face is the lack of public interest in participating, goverment is valued less the aspirations of the people should be overcome by it, provide an understanding of the importance of public participation in Formation of Regional Regulation 3 Of 2017 about the entertainment business in Wonosobo, maximizing the dissemination of the regulations and the third accommodate all the aspirations of the peopleKeywords: Public Participation; Local Regulation; Entertainment.